2015
DOI: 10.1007/s00359-015-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic modulation of social status-dependent behavioural plasticity of the crayfish avoidance reaction

Abstract: Small crayfish usually showed escape-like dart responses to mechanical stimulation of the tailfan. Following agonistic bouts with conspecifics, dominant crayfish showed a defensive-like turn response to the same sensory stimulus. During the dart response, both uropods closed and animals walked forwards with the abdomen extended, while during the turn response the uropod on the stimulated side opened and animals turned towards the stimulus source with the abdomen frequently flexed. Using an isolated nerve cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This result is similar to a winner effect that winning small animals in previous fights tend to win against large animals in the subsequent fights (Momohara et al, 2013). A decrease in cAMP level in the brain mediated by serotonin induces the winner effect (Momohara et al, 2015(Momohara et al, , 2016. At the moment, the neurochemical and physiological bases underlying the residence effect are unclear, but certain biogenic amines like serotonin could underlie this effect.…”
Section: Evidence Of Residence Effectsupporting
confidence: 59%
“…This result is similar to a winner effect that winning small animals in previous fights tend to win against large animals in the subsequent fights (Momohara et al, 2013). A decrease in cAMP level in the brain mediated by serotonin induces the winner effect (Momohara et al, 2015(Momohara et al, , 2016. At the moment, the neurochemical and physiological bases underlying the residence effect are unclear, but certain biogenic amines like serotonin could underlie this effect.…”
Section: Evidence Of Residence Effectsupporting
confidence: 59%
“…Biogenic amines are known to modulate animals’ physiological conditions and affect feeding, sexual, postural and aggressive behaviours in a wide range of arthropods, as well as vertebrate animals (Livingstone et al ., ; Weiger, ; Kravitz, ; Lesch & Merschdorf, ; Kravitz & Huber, ; Momohara et al ., , ). They also affect neural activity underlying learning and memory (Hammer & Menzel, ; Kandel, ; Schwaerzel et al ., ; Araki et al ., ; Menses & Liy‐Salmeron, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kravitz () first showed that postures resembling aggressive or submissive stance are induced by injection of serotonin or octopamine. Subsequent work has shown that winner and loser effects are also mimicked by administration of serotonin and octopamine (Momohara et al ., , ). As serotonin and octopamine receptors mostly belong to a superfamily of G‐protein coupled metabolic receptors (Hoyer et al ., ; Gerhardt et al ., ; Roeder, ; Spitzer et al ., ), their downstream second messengers could mediate winner and loser effects.…”
Section: Introductionmentioning
confidence: 99%